Upaya Meningkatkan Keaktifan Belajar Siswa melalui Model Pembelajaran Project Base Learning di SMA Negeri 4 Bojonegoro - Darmisih Darmisih; Edy Siswanto; Albrian Fiky Prakoso (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
This study aims to increase the active learning of SMA Negeri 4 Bojonegoro students through project base learning. This research is included in the type of classroom action research which includes several cycles. Each cycle includes planning, implementing actions, observing, and reflecting. The subjects of this study were students of class X-1 at SMA Negeri 4 Bojonegoro consisting of 33 students. The research instruments were observation sheets, questionnaires and documentary evidence. Data collection techniques through observation, questionnaires and documentation studies. Data analysis techniques in this study include data reduction, data selection, data simplification, and conversion of raw data from field notes. Based on the results of pre-cycle observations of student activity by 48% in the